Local anaesthesia for endovascular repair of infrarenal aortic aneurysms - Geisbüsch, Philipp; Katzen, Barry T.; Machado, R.; Benenati, J. F.; Pena, C.; Tsoukas, A. I. (European journal of vascular and endovascular surgery, 2011)
Objective - The study aimed to analyse and report the results of a ‘local anaesthesia first’ approach in elective endovascular aneurysm repair (EVAR) patients. - Material and methods - Between January 2007 and August 2010, a total of 217 continuous patients (187 men, median age 76 years, range 52-94 years) underwent elective EVAR using this approach, with predefined exclusion criteria for local anaesthesia (LA). A retrospective analysis regarding technical feasibility, mortality, complication and endoleak rate was performed. The results are reported as an observational study. - Results - LA was applied in 183 patients (84%), regional anaesthesia (RA) in nine patients (4%) and general anaesthesia (GA) in 25 patients (12%). Anaesthetic conversion from LA to GA was necessary in 14 patients (7.6%). Airway obstruction (n = 4) and persistent coughing (n = 3) were the most common causes for conversion to GA. Thirty-day mortality in the LA group was 2.7%, with 16/183 patients (8.7%) experiencing postoperative complications. All type I endoleaks (n = 5, 2.7%) occurred in patients with LA and challenging aneurysm morphologies. - Conclusions - A ‘local anaesthesia first’ strategy can successfully be applied in 75% of patients undergoing EVAR. The use of LA can impact imaging quality and thus precise endograft placement, which should be considered in patients with challenging aneurysm morphologies.